Edukasi Penguatan Peran Santri Pondok Pesantren Darul Falah Purwokerto dalam Politik Kewargaan - Pujangga Candrawijayaning Fajri; Wahyuni, Hesti Ayu; Dewi, Monica Puspa (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The purpose of this service is to increase the understanding of students at the Darul Falah Islamic Boarding School in Purwokerto regarding civic politics, which is currently experiencing a rather acute erosion, even tho civic politics is an important aspect of nationhood; it guaranties the right to life, the right to equal treatment and recognition before the law, the right to think, the right to express opinions, and the right to assemble. In this case, the method used is socialization based on a participatory approach thru lectures, discussions, and statements of attitude. The results of this service activity show that after the presentation of material on the history of santri and the rights of citizens, enthusiasm arose among the santri of Pondok Santri Darul Falah Purwokerto regarding the inherent rights and obligations of all citizens. Students can actualize civic politics by integrating religious sciences, such as by contextualizing environmental jurisprudence in response to the massive environmental damage occurring thanks to state policies. This service activity encourages the role of santri in the state, which was initially only stigmatized as being limited to the realm of seeking religious knowledge and preaching.